2019
DOI: 10.3389/fmicb.2019.01508
|View full text |Cite
|
Sign up to set email alerts
|

Feasability of Introducing a Thioether Ring in Vasopressin by nisBTC Co-expression in Lactococcus lactis

Abstract: Introducing one or more intramolecular thioether bridges in a peptide provides a promising approach to create more stable molecules with improved pharmacodynamic properties and especially to protect peptides against proteolytic degradation. Lanthipeptides are compounds that naturally possess thioether bonds in their structure. The model lanthipeptide, nisin, is produced by Lactococcus lactis as a core peptide fused to a leader peptide. The modification machinery responsible for nisin pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Some studies also focus on the engineering of key enzymes for thioether ring formation. For instance, in 2019, Kuipers OP group fused the Ser/Thr-dehydratase NisB and the cyclase NisC for nisin production to the biosynthetic pathway of vasopressin, and obtained a vasopressin analog with replacement of an original disulfide bridge with a thioether bridge, providing the proof for applying the post-translational modification systems of lanthipeptides into generation of new bioactive products ( Li et al, 2019 ).…”
Section: Mining and Biosynthetic Reconstruction Of New Lanthipeptidesmentioning
confidence: 99%
“…Some studies also focus on the engineering of key enzymes for thioether ring formation. For instance, in 2019, Kuipers OP group fused the Ser/Thr-dehydratase NisB and the cyclase NisC for nisin production to the biosynthetic pathway of vasopressin, and obtained a vasopressin analog with replacement of an original disulfide bridge with a thioether bridge, providing the proof for applying the post-translational modification systems of lanthipeptides into generation of new bioactive products ( Li et al, 2019 ).…”
Section: Mining and Biosynthetic Reconstruction Of New Lanthipeptidesmentioning
confidence: 99%
“…Lanthipeptides form a promising source of stable bioactive compounds with a broad range of biological activities ranging from antimicrobial (lantibiotics), antifungal, or antiviral activities to signaling molecules, channel regulators, and immunomodulatory, antiallodynic, anticonceptive, or anticancer activities. ,, Current genome mining methodologies , have shown that they are produced by species of all domains of life, with a broad and versatile range of topologies and diverse biosynthetic types of machinery. , The extraordinary diversity of modification enzymes and structures of the family of RiPPs provides an attractive synthetic biology platform for combining different modules of enzymes to introduce a variety of post-translational modifications in peptides. For example, it opens up the possibility of synthesizing engineered novel macrocyclic NRPS-like structures without requiring multimodular enzyme complexes for their synthesis. , Different biosynthetic machinery have been used to produce lanthipeptides with new structures and biological functions, such as the production of antimicrobials, hormones, protein inhibitors against HIV, and epitope grafting. Moreover, the expression of hybrid peptides with different leaders from RiPP machinery and the development of peptides with enhanced activity and/or stability by the introduction of lanthionine ring(s) have been demonstrated. , However, some of the modification enzymes used in previous studies display a moderate-to-high substrate specificity, thereby limiting their potential for the modification of unrelated precursor peptides. To overcome this limitation, a new group of lanthipeptide synthetases called ProcM-like enzymes is currently under investigation because of their high substrate promiscuity.…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Different biosynthetic machinery have been used to produce lanthipeptides with new structures and biological functions, such as the production of antimicrobials, hormones, protein inhibitors against HIV, and epitope grafting. 13 19 Moreover, the expression of hybrid peptides with different leaders from RiPP machinery and the development of peptides with enhanced activity and/or stability by the introduction of lanthionine ring(s) have been demonstrated. 15 , 19 25 However, some of the modification enzymes used in previous studies display a moderate-to-high substrate specificity, thereby limiting their potential for the modification of unrelated precursor peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this machinery can be used for the heterologous expression of different LanA substrates, with a special focus on lantibiotics, , a class of lanthipeptides characterized by the presence of antimicrobial activity, although also lanthipeptides with antifungal, antiviral, morphogenetic, anticonceptive, or antiallodynic functions have been described . Moreover, the lanthipeptide biosynthetic machinery has been used to design new-to-nature lanthipeptides, generating peptides with enhanced activity or stability. , The heterologous expression of lanthipeptides using the nisin biosynthetic machinery has been broadly used for the heterologous expression of newly designed antimicrobials. , However, the substrate specificity of the synthetase enzymes NisB and NisC limits the production of this type of variant compounds on a large scale. Therefore, new and promiscuous lanthipeptide synthetase enzymes with enhanced properties to fully process a large number of unrelated LanA substrates or with the ability to introduce rings with different topologies could be used for the effective heterologous production of novel bioactive lanthipeptides, either engineered variants or lanthipeptides from different (exotic) origins.…”
Section: Introductionmentioning
confidence: 99%
“…10 Moreover, the lanthipeptide biosynthetic machinery has been used to design new-to-nature lanthipeptides, generating peptides with enhanced activity or stability. 12,13 The heterologous expression of lanthipeptides using the nisin biosynthetic machinery has been broadly used for the heterologous expression of newly designed antimicrobials. 12,14−17 However, the substrate specificity of the synthetase enzymes NisB and NisC limits the production of this type of variant compounds on a large scale.…”
Section: ■ Introductionmentioning
confidence: 99%